1999
DOI: 10.1161/01.hyp.34.6.1208
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Diastolic Dysfunction in Lean and Obese Hypertensives

Abstract: Abstract-We investigated the influence of genetic predisposition to hypertension by studying the relation between insulin sensitivity and left ventricular (LV) mass and function in untreated lean and obese hypertensives. We selected 50 lean hypertensives with normotensive parents (negative family history of hypertension [FϪ]), 64 lean hypertensives with 1 or both parents hypertensive (positive family history of hypertension [Fϩ]), 40 obese FϪ hypertensives, and 43 obese Fϩ hypertensives. The 4 groups were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In addition, some of these studies reported that the relation between the two was independent of LVMI (31)(32)(33). Studies on the association between insulin and LV mass in humans have yielded conflicting results (23,27,31,(33)(34)(35)(36)(37)(38)(39)(40), but recent studies have demonstrated that neither plasma insulin concentration nor insulin sensitivity is an independent determinant of LVMI in nondiabetic subjects (38,39). Therefore, the findings in our study might have been at least partly caused by hyperinsulinemia linked to glucose intolerance and hypertension.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In addition, some of these studies reported that the relation between the two was independent of LVMI (31)(32)(33). Studies on the association between insulin and LV mass in humans have yielded conflicting results (23,27,31,(33)(34)(35)(36)(37)(38)(39)(40), but recent studies have demonstrated that neither plasma insulin concentration nor insulin sensitivity is an independent determinant of LVMI in nondiabetic subjects (38,39). Therefore, the findings in our study might have been at least partly caused by hyperinsulinemia linked to glucose intolerance and hypertension.…”
Section: Discussionmentioning
confidence: 52%
“…Many studies have reported that the existence of hyperinsulinemia or insulin resistance is related to LV diastolic dysfunction in nondiabetic hypertensives (27,(30)(31)(32)(33)(34)(35). In addition, some of these studies reported that the relation between the two was independent of LVMI (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in TGFb1 values and LVM/h 2.7 and a higher prevalence of subjects with left ventricular hypertrophy were found in the subset of hypertensives with diastolic dysfunction in comparison with patients with normal diastolic function. According to literature data [37][38][39][40] and to higher prevalence of LVH found in our hypertensives with altered diastolic function, TGFb1 overproduction might be able to affect diastolic function through an altered left ventricular geometry. Surprisingly, in our study, multivariate analysis indicated an independent role of TGFb1 in the occurence of alteration in left ventricular filling.…”
Section: Left Ventricular Filling Abnormalities and Obesity-associatementioning
confidence: 53%
“…39 Obviously, the present study does not explore the pathophysiology of the possible link between TGFb1 overproduction, hyperinsulinaemia or insulin resistance, RAS hyperactivity and diastolic dysfunction, but we could hypothesize that TGFb1 overproduction may be able to affect left ventricular filling early in obese hypertensives, independent of the effects related to increased LVM. This hypothesis might be supported by the statement that, with the fibrotic remodelling process, an increase in the stiffness of left ventricular myocardium can lead to an early impairment of the diastolic function.…”
Section: Left Ventricular Filling Abnormalities and Obesity-associatementioning
confidence: 87%